2005
DOI: 10.1159/000087034
|View full text |Cite
|
Sign up to set email alerts
|

Stress Symptoms Induced by Repeated Morphine Withdrawal in Comparison to Other Chronic Stress Models in Mice

Abstract: The present study was aimed at evaluating chronic stress models in mice with special attention to morphine treatment. We hypothesized that repeated periods of drug withdrawal induce chronic stress. To verify this hypothesis, mice were made dependent on morphine and then subjected to several types of repeated withdrawal. Body weight reduction, thymus involution, adrenal gland enlargement and activation of the hypothalamo-pituitary-adrenal axis were used as signs of chronic stress. The changes were compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 86 publications
(56 reference statements)
3
17
0
Order By: Relevance
“…In agreement with previous studies, evaluation of serum corticosterone concentration showed an increase in corticosterone level following 4 hr morphine withdrawal in dependent animals [6,7].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies, evaluation of serum corticosterone concentration showed an increase in corticosterone level following 4 hr morphine withdrawal in dependent animals [6,7].…”
Section: Discussionsupporting
confidence: 93%
“…Morphine withdrawal is associated with activation of the HPA [5]. A study has shown that repeated short periods of drug withdrawal (24 or 72 hr) in morphine-dependent mice represent a mild stress load [6] and animals undergoing acute (12 hr) morphine withdrawal displayed a potentiated and prolonged corticosterone response to restraint [7].Previous studies in both animal and human beings indicate that stress and glucocorticoids modulate various phases of memory processing [8][9][10]. Acute administration of glucocorticoid hormones enhances memory consolidation or acquisition in both animals and human beings in a dosedependent manner but usually impairs the retrieval of previously acquired information [11][12][13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic administration of morphine may result in tolerance to the stimulatory effect of the opioid on the HPA axis (Buckingham & Cooper 1984, Ignar & Kuhn 1990; the secretion of pituitary ACTH in response to (other) stressors may become suppressed (Briggs & Munsoon 1955, Buckingham & Cooper 1984. In contrast, chronic intermittent (e.g., twice daily) administration of morphine may lead to chronic stress probably as a consequence of repeated withdrawal (Houshyar et al 2001a, Zelena et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most susceptible risk factors in this disease is any kind of emotional stress [4]. Opioid withdrawal can be an origin of stress for opioid addicted patients [9]. Therefore the stress that stem from opioid withdrawal may be an underlying cause of Graves' disease.…”
Section: Discussionmentioning
confidence: 99%